RADIOGRAPHIC EVALUATION OF PERIAPICAL STATUS AND FREQUENCY OF ENDODONTIC TREATMENT IN A TURKISH POPULATION:A RETROSPECTIVE STUDY* - Melek TAŞSÖKER; Faruk AKGÜNLÜ (Istanbul University, 2016)
Purpose: The aim of this study was to determine the frequencies of apical periodontitis and endodontic treatment in a Turkish population using a retrospective analysis of orthopantomograms. Materials and Methods: The sample consisted of orthopantomographs of 250 subjects who had been referred to our clinic for an initial visit between the years of 2013 and 2014. The periapical status of all teeth (with the exception of third molars) was examined using periapical index scoring system (PAI). Data were analyzed statistically using the Chi-squared test at the significance level of p<0.05. Results: The study sample comprised 6196 teeth belonging to 250 patients. Out of 6196 examined teeth, the frequencies of apical periodontitis and endodontic treatment was 1.8% and 3.7%, respectively. Gender had no effect on the presence of apical periodontitis or the frequency of endodontic treatment. The frequency of apical periodontitis and endodontic treatment increased with age, but it did not show statistical significance among different age groups. Conclusion: This study provides epidemiological data about apical periodontitis and endodontic treatment in a Turkish population.